Using framing to foster creativity in learning: Reflective tool to analyze and discuss practice - Jónsdóttir, Svanborg Rannveig; Macdonald, Marey Allyson (Frontiers in Education, 2022)
Over the last few decades in Iceland several models have been devised for use as pedagogic devices. In this article we present a model that has been used to analyze pedagogy in innovation and entrepreneurial education in 2011 and in two recent participatory action research projects in Iceland. The model draws on some of Basil Bernstein´s better-known concepts and theories, such as “framing and classification” and “power and control.” Through multiple iterations, this model has developed into a specific analytical tool initially emerging through a research project in 2011. Specific tools were defined for particular uses such as to identify freedom versus control in the classroom and/or other school spaces and to explore how these events manifest in practice. We present how the tool was used in the three studies. We share how the action researchers, who taught different subjects at four different school levels, used the model to support their understanding of cultivating creativity in their students’ learning. We conclude that the model can be used by teachers at any school level to identify which elements they control in teaching and learning processes and how they can support students´ creativity.